How Efficiently is Capital Created? Evidence from Property Registration Reform in Egypt - Ibrahim, Jamal Haidar (World Bank, Washington, DC, 2012)
One tool for enhancing economic growth is a simple property registration process. Many developed countries, and countries on their way toward development, have simple, inexpensive, and fast property registration processes. The benefit of such a tool is driven by this thinking: low property registration fees encourage every property holder to receive a formal title. The poor especially will benefit, because they can use their property as collateral, start doing business, and achieve some of their dreams. Recognizing the importance of property registration to the ease of doing business, the Egyptian ministry of investment spotted a relevant reform. A reform strategy was immediately set up. Two problem areas were identified: the cost and quality of procedures to register a property. In Cairo one year ago, registering a property would cost on average 5.9 percent of its value, causing 90 percent of property to be either unregistered or registered at underestimated values.